Investigation on Phytochemicals, Anthelmintic and Analgesic Activities of Smilax zeylanica Linn. Leafy Extracts - Kumar Jena, Prabhat; Shankar Nayak, Bhabani; Chandra Dinda, Subas; Ellaiah, P. (Asian Journal of Chemistry, 2011)
The present study involves the preliminary investigation of phytochemical constituents, acute toxicity study and the anthelmintic activity of different extracts of leaves of S. zeylanica using petroleum ether, diethyl ether, chloroform and methanol as solvents. The study was also extended to evaluate analgesic activity of different extracts of leaves of S. zeylanica using petroleum ether, chloroform and methanol as solvents. The phytochemical studies indicated that the tests for glycosides, alkaloids, tannins, triterpenoids and sterols compounds were positive for all the extracts except chloroform extract, while the tests for carbohydrate, proteins, saponins, lipids and flavonoids were negative for all extracts. The various doses of solvents extracts were evaluated for their anthelmintic activities on adult Indian earthworms, Pheretima postuma. All extracts exhibited the anthelmintic activity at 10 mg/mL concentration and the activities were well comparable with the standard drug, piperazine citrate. The analgesic activity of above extracts was evaluated by using tail immersion method in Swiss albino mice. All the extracts showed analgesic activity that was comparable with standard drug (aspirin). Among all the solvent extracts, methanolic extract showed better anthelmintic as well as analgesic activities. The data were verified as statistically significant by using one way ANOVA at 5 % level of significance (p < 0.05).